PERTIMBANGAN HAKIM DALAM PENOLAKAN DISPENSASI KAWIN PERSPEKTIF TEORI SISTEM HUKUM DI PENGADILAN AGAMA - Kurniawati, Aisyah Hafidah (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
Child marriage could be a marriage conducted by children or teenagers, and its usage must get authorization from the Devout Court Judge. The dismissal of marriage allotments is an vital issue within the legal framework in Indonesia, especially within the Devout Courts, which regularly confront a problem between person interface and legitimate security for children. This inquire about points to analyze the judges' contemplations in dismissing marriage allotments through the viewpoint of lawful framework hypothesis. Employing a subjective approach with a case consider strategy, this inquire about looks at how components of the legitimate system-structure, substance, and legitimate culture-play a part in judges' decision-making at the Devout Court. The discoveries show that the dismissal of marriage agreements is frequently based on the security of children's rights and adherence to the legitimate limits set forward in Law Number 16 of 2019 concerning Revisions to Law Number 1 of 1974 on Marriage. In expansion, socio-cultural components and devout understanding moreover impact judges' viewpoints in keeping up a adjust between national legitimate standards and Islamic values. The dismissal moreover reflects the legitimate responsiveness to the requests for child assurance and the avoidance of the negative impacts of early marriage. In this way, the lawful framework hypothesis gives a significant conceptual system for understanding the complexities of judges' contemplations within the Devout Courts with respect to marriage allotments. Keyword: Marriage allotment, judge's thought, Devout Court, legitimate framework theory, child security.